PENGARUH PRODUK DAN PROMOSI TERHADAP PENINGKATAN PENJUALAN PADA USAHA IBU-IBU DESA BAKARAN BATU, DELI SERDANG - Ukur Ardianta Ginting, Samuel Tenang; Nurbeti; Aulia Rahma, Ajeng; Orlando Ginting, Giell (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, Universitas Muslim Nusantara Al-Washliyah, 2024)
ABSTRACT Village development implementing self-reliance through mutual cooperation values ​​is part of the uniqueness of village communities that remain sustainable. Bakaran Batu is a village located in North Sumatra Province, Deli Serdang Regency, Lubuk Pakam District, where mothers continue to strive to advance the village and empower the village community's economy by continuing to involve all major stakeholders in the village. Several problems arise from the high rate of economic growth, so that in every effort they must think about Products and Promotions in all fields according to the needs of the community, resulting in an increase in sales. The purpose of this study was to determine the effect of products and promotions on increasing sales in the businesses of mothers in Bakaran Batu Village, Deli Serdang. The independent variables (independent X) consist of Products, and Promotions, and the dependent variable (dependent Y) is Sales Increase, then find the dominant variable. Quantitative descriptive analysis is a method in this study. The results of the analysis of multiple regression show that Products (X1), Promotions (X2), each can affect Sales Increase by looking at the magnitude of the regression coefficient obtained. Quantitative research methods are used to emphasize testing the theory used with research variables measured, data analyzed using statistical procedures, with the help of SPSS Software Applications. From the results of the partial coefficient test (r) it will be obtained that the independent variable is more dominant than the dependent variable. The targeted output of this proposed research is to be published in a Research Journal that has the Journal Online System (OJS). Therefore, the researcher is interested in raising a research title